Pragmatic Failures in English Among Graduate International EFL Students - Bolad, Mahmoud Amjad Muhammad (Samudra Publisher, 2025)
This study investigates the types and causes of pragmatic failure in English communication among postgraduate international EFL students at Universitas Muhammadiyah Surakarta (UMS). Using a qualitative descriptive method, data were gathered through classroom observations and semi-structured interviews with five culturally diverse participants. Thematic analysis revealed six main categories of pragmatic failure: impolite direct requests, blunt refusals, inadequate apologies, misinterpretation of indirect speech, inappropriate politeness norms, and limited learner awareness. These failures were often shaped by cultural transfer, insufficient pragmatic awareness, and lack of exposure to authentic language use. The study not only identifies recurrent pragmatic issues but also examines their underlying causes and offers implications for explicit instruction. The findings suggest the importance of integrating pragmatic awareness into EFL teaching to enhance students' communicative competence in both academic and intercultural contexts. The study contributes to the development of effective communication strategies in multicultural academic contexts.